2022
DOI: 10.3390/ijerph192416645
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity, Core Self-Evaluation, School Adaptation, and Mental Health Problems in Migrant Children in China: A Chain Mediation Model

Abstract: (1) Background: The present study investigated the relationships between social identity, core self-evaluation, school adaptation, and mental health problems in migrant children, and the mechanism underlying these relationships; (2) Methods: The participants were migrant middle school students in China. Data analysis was conducted using SPSS version 26. A survey comprising the social identity scale, core self-evaluation scale, school adaptation scale, and mental health scale MMHI-60 was deployed; (3) Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…This study demonstrated that the current subjective well-being of migrant workers’ accompanying children in Jiangxi province is moderate overall and significantly lower than that of urban children. Previous studies have found that conclusions consistent with the present study, 3 , 38 however, other studies have also found no significant difference between migrant workers’ accompanying children and urban children in terms of mental health outcomes. The present study not only provided new data support for the former type of research, but also revealed an important reason.…”
Section: Discussionsupporting
confidence: 89%
“…This study demonstrated that the current subjective well-being of migrant workers’ accompanying children in Jiangxi province is moderate overall and significantly lower than that of urban children. Previous studies have found that conclusions consistent with the present study, 3 , 38 however, other studies have also found no significant difference between migrant workers’ accompanying children and urban children in terms of mental health outcomes. The present study not only provided new data support for the former type of research, but also revealed an important reason.…”
Section: Discussionsupporting
confidence: 89%